Systematic Comparison of Nanopore and Illumina Sequencing for the Detection of Plant Viruses and Viroids Using Total RNA Sequencing Approach - Pecman, Anja; Adams, Ian; Gutiérrez-Aguirre, Ion; Fox, Adrian; Boonham, Neil; Ravnikar, Maja; Kutnjak, Denis (Frontiers in Microbiology, 2022)
High-throughput sequencing (HTS) has become an important tool for plant virus detection and discovery. Nanopore sequencing has been rapidly developing in recent years and offers new possibilities for fast diagnostic applications of HTS. With this in mind, a study was completed, comparing the most established HTS platform (MiSeq benchtop sequencer - Illumina), with the MinION sequencer (Oxford Nanopore Technologies) for the detection of plant viruses and viroids. Method comparisons were performed on five selected samples, containing two viroids, which were sequenced using nanopore technology for the first time and eleven plant viruses with different genome organizations. For all samples, sequencing libraries for the MiSeq were prepared from ribosomal-RNA depleted total-RNA (rRNA-depleted totRNA) and for MinION sequencing, direct RNA sequencing of totRNA was used. Moreover, for one of the samples, which contained five different plant viruses and a viroid, three additional variations of sample preparation for MinION sequencing were also used: direct RNA sequencing of rRNA-depleted totRNA, cDNA-PCR sequencing of totRNA and cDNA-PCR sequencing of rRNA-depleted totRNA. Whilst direct RNA sequencing of total RNA was the quickest of the tested approaches, it was also the least sensitive: using this approach, we failed to detect only one virus that was present in a sample at an extremely low titer. All other MinION sequencing approaches showed improved performance with outcomes similar to Illumina sequencing, with cDNA-PCR sequencing of rRNA-depleted totRNA showing the best performance among tested nanopore MinION sequencing approaches. Moreover, when enough sequencing data was generated, high quality consensus viral genome sequences could be reconstructed from MinION sequencing data, with high identity to the ones generated from Illumina data. The results of this study implicate that, when an appropriate sample and library preparation is selected, nanopore MinION sequencing could be used for the detection of plant viruses and viroids with similar performance as Illumina sequencing. Taken as a balance of practicality and performance, this suggests that MinION sequencing may be an ideal tool for fast and affordable virus diagnostics.